THE EFFECT OF TIME SINCE INJURY ON THE PROGRESSION OF ROTATOR CUFF ARTHROPATHY OF THE SHOULDER (RETROSPECTIVE STUDY) - Bohdan, Sergiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Rotator cuff disease is a disease of the shoulder joint, which is c haracterized b y i nsufficient f unction o f t he r otator c uff of the shoulder, degenerative changes in the joint capsule and migration ( displacement) o f t he h umeral h ead. T he o bjective of the study is to investigate the influence of time since injury on the progression of rotator cuff arthropathy of the shoulder joint. Materials and methods. We included 91 patients in the study who, at the time of examination, had rotator cuff arthropathy of varying degrees. The age of the patients ranged from 35 to 80 years. The average age was (48.2 ± 19.8) years. The inclusion criteria for the study were as follows: the presence of rotator cuff arthropathy of any degree, clear indication to the patient of the time since the injury, the presence of an MRI scan with a magnetic field strength of 1.5 Tsl, age 35 to 80 years, the absence of concomitant pathology of the shoulder (homarthrosis, calcifying tendinitis and any bone pathology of the proximal epimetaphysis of the humerus. The degree of rotator cuff arthropathy, damage to the soft tissue structures of the shoulder joint, and the time from injury to the patientʼs visit were determined. Results. The vast majority of patients had stage 2 rotator cuff arthropathy — 60.4 %, a slightly smaller number of patients had stage 1. rotator arthropathy — 23.1 %, patients with 3–5th degree. rotator arthropathy was significantly less — a total of 16.5 %. With an increase in the average terms from the moment of injury, the degree of rotator arthropathy increases. For the development of rotator arthropathy of the 1st degree, an average term of (5.16 ± 1.54) months after injury is required, while for the development of rotator arthropathy of the 4th degree, an average term of (11.25 ± 4.6) months after injury is required. Conclusions. There is a weak (r = 0.31; p = 0.051), but significant dependence of the influence of the term from the moment of injury on the degree of rotator arthropathy. Thus, with an increase in the terms from the moment of injury, the degree of rotator arthropathy of the shoulder joint may also increase.